Neogene planktonic Foraminiferal turnover in the Mediterranean Area - Lirer F.; Iaccarino S.; Pelosi N.; FORESI, LUCA MARIA (Cagatay Z., Zabci C, 2013)
The Neogene Peri od is characterised by several oscillations in c1imate and related tums in fossils community, and planktonic Foraminifera represent an important tool to monitor these climatic changes. In particular, tbe planktonic foraminiferal populations of the Mediterranean area show pronounced oscillations on a variety of temporal scales from Milankovitch timescale to millionyear timescale. An analysis of planktonic foraminiferal literature data and species quantitative distribution datasets from Mediterranean on land sections and deep marine cores, calibrated vs the Geological Time Scale 2012, revealed the occurrence of four main increases in turnover during the Miocene, centred at 21.8 Ma (Aquitanian tumover), 15.6 Ma (Middle Mioeene tumover), 11.2 Ma (early Tortonian tumover) and 7 Ma (early Messinian tumover). Contrarily, the Plio-Pleistoeene time interval is eharacterised by a generai deereases in planktonie foraminiferal turnover with three minima centred at 4.8 Ma (Zanclean turnover), 2.9 Ma (Piaeenzian tumover) and at 1.2 Ma (Calabrian turnover).Power speetral analysis revealed the existence of tumover cycles with periods of 1.3, 1.0 and 2.0 Ma.